Non-intrusive defect detection of multiple parallel cables - Lim, Shaun Zhi Hao (2019)
The aim of this study was to simulate and study the results of an SMRT designed power network cables simulation, proposing defect monitoring classified as impedance characteristics, such as inductive and capacitive characteristics over frequency measurements of 1MHz to 10MHz. This paper investigated using a designed probe using a Vector Network Analyzer (VNA) and two-port ABCD network parameters to detect defects along multiple parallel cables to a high-power station. In contrast to the inductive coupling method, with the use of two-port ABCD network approach parameters, it eliminated the need for disconnecting the power supply for standardized premeasurement calibration, and a 1-time calibration is adequate for the proposed ABCD network approach. It can also detect changes in-circuit impedance of the cables under varying conditions of operation, thus suitable in translating to practical use such as repair or replacement work in real-time monitoring of non-intrusive defect detection along multiple parallel cables.